2022
DOI: 10.3389/fpsyt.2022.886538
|View full text |Cite
|
Sign up to set email alerts
|

Improving University Students' Mental Health During the COVID-19 Pandemic: Evidence From an Online Counseling Intervention in Italy

Abstract: BackgroundThe mental health of university students is significantly affected when faced with public health emergencies and requires specific interventions to help support and prevent any long-lasting effects that the pandemic may have on their mental health status. This study aims to evaluate the impact of an online individual counseling intervention provided by the University of Foggia and carried out during the COVID-19 pandemic on the mental health status of a sample of university students.Methods32 Italian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 105 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…All of the RCTs investigated the effectiveness of online psychological interventions declined in several ways: mostly programs based on online modules (e.g., [ 94 , 95 , 96 , 97 , 98 ]), websites interaction (e.g., [ 99 ]), use of mobile apps (e.g., [ 100 ]), and face-to-face meetings followed by online exercises and interaction (e.g., [ 101 ]). Only one quasi-experimental study without a control group tested the effectiveness of online counseling delivered by a physical counselor due to pandemic needs [ 22 ]. Except for the latter studies [ 22 , 101 ], all of the other programs did not require intervention delivery by a physical counselor and usually had a weekly schedule.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the RCTs investigated the effectiveness of online psychological interventions declined in several ways: mostly programs based on online modules (e.g., [ 94 , 95 , 96 , 97 , 98 ]), websites interaction (e.g., [ 99 ]), use of mobile apps (e.g., [ 100 ]), and face-to-face meetings followed by online exercises and interaction (e.g., [ 101 ]). Only one quasi-experimental study without a control group tested the effectiveness of online counseling delivered by a physical counselor due to pandemic needs [ 22 ]. Except for the latter studies [ 22 , 101 ], all of the other programs did not require intervention delivery by a physical counselor and usually had a weekly schedule.…”
Section: Resultsmentioning
confidence: 99%
“…Only one quasi-experimental study without a control group tested the effectiveness of online counseling delivered by a physical counselor due to pandemic needs [ 22 ]. Except for the latter studies [ 22 , 101 ], all of the other programs did not require intervention delivery by a physical counselor and usually had a weekly schedule. Some of them were ACT-oriented (e.g., [ 97 , 98 , 101 ]) and CBT-based (e.g., [ 96 , 102 ]), offering a wide range of evidence-based techniques and options for the promotion of well-being and the transdiagnostic prevention of common mental disorders and psychological distress among university students (e.g., [ 94 , 95 , 96 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The provision of online counseling services, mental health resources, and peer support networks could have promoted the exploration and utilization of healthier coping mechanisms, leading to a decrease in selfblame. Furthermore, the emphasis on resilience-building and psychological well-being in educational institutions during the pandemic may have influenced university freshmen to adopt coping strategies that promote self-compassion and self-care [55,56]. The recognition of the importance of self-acceptance and seeking external support may have contributed to the reduction in the use of self-blame as a coping mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond anxiety and depressive symptoms, one meta-analysis revealed that COVID-19 patients had high rates of post-traumatic stress disorder, insomnia, somatization and fear [ 13 ]. However, compared with studies on the mental health of the general population, COVID-19 survivors, or healthcare personnel during COVID-19 pandemic, relatively few studies have investigated the mental health of inpatients with COVID-19 during their stay [ [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Moreover, the existing results with COVID-19 inpatients varied widely, with the reported prevalence of anxiety and depression ranging from 19 % to 60 % and from 13 % to 80 %, respectively [ [15] , [16] , [17] , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%